Role of hematological indices as predictors of systemic inflammation in dermatology - Sanmitra Aiholli; Keshavmurthy A Adya; Arun C Inamadar (Wolters Kluwer Medknow Publications, 2024)
Hematological indices have long been used in a variety of conditions as indicators of systemic inflammation. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are inexpensive tools in predicting severity and disease activity in acute coronary syndrome, malignancy, coronavirus disease 2019 (COVID-19) illness, and other autoimmune conditions. Evidence suggests that such hematological indices can be used in various dermatoses as predictors of systemic inflammation, to assess the severity of the disease, prognosis, and treatment response.